Many-body van der Waals interactions in wet MoS2 surfaces. (1st June 2022) - Shao, Xuecheng; Umerbekova, Alina; Jiang, Kaili; Pavanello, Michele
Abstract: Many-body dispersion (MBD), and generally many-body correlation effects, have emerged in recent years as key contributions to intermolecular interactions in condensed phases affecting nearly every field in the molecular sciences. Ab initio electronic structure methods are the golden standard of material science but unfortunately they are too computationally expensive for evaluating MBD in such complex systems as liquid–solid interfaces. In this work, we leverage subsystem time-dependent DFT's rigorous decomposition of the system's response function into subsystem contributions to evaluate the effect of many-body correlation effects (which include dispersion) for each water molecule in a model of wet MoS2 surface. The optical spectra and and to a lesser extent the effective molecular C 6 coefficients display a dependence on a handful of order parameters describing the liquid as well as the distance and orientation of the molecules with respect to the surface. Overall, we provide an unprecedented, granular analysis of many-body correlation effects for wet MoS2 which will be useful for developing more approximate models, such as force fields and other multi-scale methods for water–surface interactions.